Exploring Generation Z's Opinions on Internet Network Quality - Nst, Fakhrunnisa Humairo; Siregar, Yulianti; Setyanti, Rizky Avrilia; Nurbaiti (Outline Publisher, 2026)
This study aims to explore Generation Z's perceptions of internet network quality on campus. The research background is based on this generation's high dependence on digital technology for academic, social, and entertainment activities. The method used was descriptive qualitative research with purposive sampling, involving students from the Faculty of Islamic Economics and Business (FEBI) at UIN North Sumatra as respondents. Data were collected through interviews using Google Forms and analyzed using a thematic analysis approach. The results showed that most students use the internet for more than seven hours per day and assess the network quality on campus as still suboptimal, particularly in terms of signal stability and coverage. Most respondents also stated that network quality directly impacts productivity and learning motivation. This study concludes that improving internet network infrastructure on campus is a strategic necessity to support the effectiveness of digital learning and the academic activities of Generation Z in the modern era.